Women's and male partners' socio-demographic and economic characteristics associated with contraceptive decision making in Nigeria - David Aduragbemi Okunlola (BMC, 2022)
Abstract Background Women's ability to make contraceptive decision can determine their contraceptive use which can improve their reproductive health and career. Improvement in such ability can increase contraceptive prevalence in Nigeria. However, factors that promote contraceptive decision-making among women are scarcely studied. This study examined factors associated with women's individual or joint contraceptive decision-making in Nigeria. Methods Secondary (cross-sectional) data were analysed. The data were extracted from the individual recode file of the 2018 Nigeria Demographic and Health Survey (DHS). Partnered women (i.e., currently married or living with a partner) aged 15-49 years and currently using contraceptives before the survey were considered. They constituted 4,823 in total. Their data were analysed using frequency and percentage distributions of variables, Chi-square tests of independence and multinominal logistic regression. Results Findings reveal that 23% (1,125) of women made their own contraceptive decision, nearly 67% (3,213) were joint decision makers, and 10% (491) stated that their male partners had decided for them. The probability of solely making contraceptive decision and being a joint decision maker (relative to being a male partner's decision) was higher among women above 29 years and aged 30-34 years (than women aged 15-24 years) respectively as well as among the employed (than the unemployed) and among those from Yoruba ethnic group (than their counterparts from Hausa/Fulani/Kanuri/Beri Beri) respectively. The probability of being responsible for contraceptive decision (than being the male partner's decision) was higher among women from the Igbo group and women whose male partners desired more children (than those with the same number of desired children) respectively. The probability of being the main decision maker (relative to being the male partner) was lower among women in the poorer (RRR = 0.39; 95%CI = 0.21-0.73; p = 0.01), middle (RRR = 0.47; 95%CI = 0.25-0.90; p = 0.02) and richest (RRR = 0.41; 95%CI = 0.20-0.82; p = 0.01) groups respectively, than the poorest women. The probability of being a joint decision maker was higher among women with secondary education (than the uneducated), practised Christianity (than the Muslims/ others), and among those residing in the North West region (than those in North East) respectively. However, the probability of being a joint decision-maker was lower among women whose partners desire more children and those who did not know their partners' desires. Conclusions Women's age, highest level of education, employment status, wealth index, ethnicity, religion, region of residence and male partners' desire for children are associated with contraceptive decision making respectively. There is a need for reproductive empowerment interventions in Nigeria that devise effective ways of improving contraceptive decision-making power of partnered women aged 15-24 years, unemployed, in the poorer and richest groups, from the Hausa/Fulani/Kanuri/Beri Beri ethnic group, practising Islam/ other religions, have the same fertility desire as their partners and those who do not know their male partner's desire for children respectively. Women whose partners desire more children should be empowered to participate effectively in contraceptive decision making.